The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s43856-023-00297-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-disaggregated effectiveness data reporting in COVID-19 vaccine research: a systematic review

Abstract: Background Sex and gender are believed to influence vaccine response. Yet, the relationship between sex and gender and COVID-19 vaccine efficacy is poorly understood and remains under-investigated. Methods We conducted a systematic review to determine whether and to what extent post-approval COVID-19 vaccine effectiveness (VE) studies report sex-disaggregated VE data. We searched four publication and pre-publication databases and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…For example, one systematic review found that only 8.8% of post-approval evaluations provided such results. 38 These findings are supported by another review, which showed that only 24% of experimental and observational studies of COVID-19 VE reported sex-stratified primary outcome data. 37 The heterogeneity of study populations and approaches to estimating VE, and the variety of vaccines evaluated, prevented authors from such studies meta-analyzing VE estimates.…”
Section: Discussionmentioning
confidence: 76%
“…For example, one systematic review found that only 8.8% of post-approval evaluations provided such results. 38 These findings are supported by another review, which showed that only 24% of experimental and observational studies of COVID-19 VE reported sex-stratified primary outcome data. 37 The heterogeneity of study populations and approaches to estimating VE, and the variety of vaccines evaluated, prevented authors from such studies meta-analyzing VE estimates.…”
Section: Discussionmentioning
confidence: 76%
“…However, no significant differences in vaccine effectiveness were observed for all outcomes across genders, as previously reported by other studies [ 62 , 63 ], with a similar dose–response trend for both genders. The need for gender-disaggregated data on the effectiveness and safety of COVID-19 vaccines has been highlighted [ 63 , 64 , 65 ], with consideration of the higher levels of vaccine hesitancy found among females across several surveys [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, Europe PMC adoption as a search engine for preprints in systematic reviews of the research literature has been referenced by numerous studies [62][63][64][65][66][67][68][69][70][71].…”
Section: Supporting Preprints Inclusion In Meta-analyses and Systemat...mentioning
confidence: 99%
“…Systematic reviewers can export all or a selection of search results in various data formats including XML and CSV. As a result, Europe PMC adoption as a search engine for preprints in systematic reviews of the research literature has been referenced by numerous studies [62][63][64][65][66][67][68][69][70][71].…”
mentioning
confidence: 99%